2007
DOI: 10.1513/pats.200607-141jg
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Sarcoidosis: Candidate Genes and Genome Scans

Abstract: Human leukocyte antigen class II allele associations and T-cell receptor beta chain bias in sarcoidosis suggest a specific diseasetriggering antigen exposure in a genetically susceptible host. The cause of sarcoidosis has been elusive, but genetics provides one of the few promising avenues to further our understanding. We review the association studies and genome scans used to identify the genes involved in sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 127 publications
0
45
0
4
Order By: Relevance
“…Conversely, in the previously published GWAS using the Affymetrix 5.0 chip [9], the lead SNP rs10484410 itself was not included, but rs1044670 (SNP_A-1824553; p59610 -3 ) was found to be strongly associated in the fine-mapping stage. However, the SNP ranked only very low in the previous GWAS (rank 6,229). The results of the validation stage were verified using TaqMan genotyping as an independent technology (.99.8% genotype concordance).…”
Section: Gwas Analysesmentioning
confidence: 92%
See 1 more Smart Citation
“…Conversely, in the previously published GWAS using the Affymetrix 5.0 chip [9], the lead SNP rs10484410 itself was not included, but rs1044670 (SNP_A-1824553; p59610 -3 ) was found to be strongly associated in the fine-mapping stage. However, the SNP ranked only very low in the previous GWAS (rank 6,229). The results of the validation stage were verified using TaqMan genotyping as an independent technology (.99.8% genotype concordance).…”
Section: Gwas Analysesmentioning
confidence: 92%
“…The genetic underpinning of sarcoidosis is further supported by known genetic risk factors located in the human leukocyte antigen (HLA) region (reviewed in [6]) and the discovery of the first confirmed susceptibility gene butyrophilin-like 2 (BTNL2; MIM 606000) on chromosome 6 [7,8]. Besides these disease loci, numerous association studies of potential candidate regions suggested additional susceptibility genes, such as the chemokine receptors chemokine receptor 2 (CCR2; MIM 601267) and chemokine receptor 5 (CCR5; MIM 601373), the tumour necrosis factor-a (TNFA; MIM 191160), and several other HLA loci (for a review see [4,6]). However, many of these show conflicting results or await replication.…”
mentioning
confidence: 99%
“…Current theory suggests that the disease develops in genetically predisposed hosts who are exposed to certain environmental agents that trigger an exaggerated inflammatory immune response leading to granulomas formation [1]. Candidate genes associated with sarcoidosis include human leukocyte antigens (HLA), chemokine receptor CCR2, Clara cell 10-kDa protein, costimulatory molecules CD80 and CD86, complement receptor CR1, cytokines interleukin-1, interleukin-18, and tumor necrosis factor-␣, and Toll-like receptor 4 [2]. Most of these candidates regulate antigen processing, antigen presentation, and inflammatory cell activation and recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, HLA-DQB1*0201 and HLA-DRB1*0301 are strongly associated with acute disease and a good prognosis [18]. The results of studies of non-HLA candidate genes have been inconsistent [19]. Genes encoding for tumor necrosis factor α (TNF-α), interferon-γ, and chemokine receptors are logical candidates on the basis of their functions, but associations with sarcoidosis have not been confirmed [20,21].…”
Section: Genetic and Familial Associations In Sarcoidosismentioning
confidence: 99%